Photo-lineament Patterns Applied to the Morphostructural Analysis of Mamanguape River Watershed, Paraíba, Northeast of Brazil - Gonçalves, Rhandysson Barbosa; Fonseca, Drielly Naamma; Correa, Antonio Carlos de Barros (Revista do Departamento de Geografia, 2017)
The Mamanguape River watershed lies in the physiographic context of the passive margin of Northeastern Brazil, whose geomorphological evolutionary history is linked to the events following the opening of the South Atlantic Ocean and the consequent South America vs. Africa separation. Its landforms are characterized by alternating topographic highs and lows, transversally to the coast-line, in agreement with geologic lineaments, inherited from ancient underlying structures, thus establishing a horst-graben topography. This study aims at contributing to the identification of local landforms and their evolution, which resulted in the deposition of sediments throughout the Neogene, as well as helping understand how such deposits suffered surface readjustments in response to neotectonics influences. Photolineaments were identified by means of the extraction of linear features from shaded-relief digital elevation models created from SRTM data. Based on the cartographic results, it was possible to recognize that to the North of the watershed morphostructures are tilted concordantly to the SW-NE and WSW-ENE trends of the major shear zones and pluton placement trends of the area. Such trends also exert control upon the arrangement of drainage network. In the mid- and lower sectors of the basin lineaments display an E-W trend, as a result of the super-imposition of the regional structural trend on the landforms, as well as of the relief reactivation following the continental rifting. Such rejuvenation pulses also control the asymmetric character of the watershed and the tilting of the landforms towards the coastline.